Пословицы и поговорки об учебе и труде: справочник школьника / О. Д. Ушакова - Ушакова О. Д. (Литера, 2010)
Экземпляры: ф.5 (20130430) / Инвентарный номер: 44393 / Цена: 55.00 / Авт.знак: У 93 / ГРНТИ: 17.71 / ББК: 82